An Emerging, Neglected and Underestimated Zoonotic Parasitic Ocular Infestation: A Comprehensive Review on Thelaziasis - Kasarla, Rajeshwar Reddy; Adhikari, Shristi Raut; Ghimire, Kripa; Pathak, Laxmi (Journal of Universal College of Medical Sciences, 2021)
Human thelaziasis is an emerging insect-borne zoonotic ocular parasitic infestation, occur more commonly in rural communities with poor living and low socioeconomic living, and mainly affects the children and old age people, where humans live in close proximity with animals. Human thelaziasis is caused by both Thelazia callipaeda and Thelazia californiensis. T. callipaeda lives under the eye lids, nictitating membranes, orbit, conjunctival sac, lachrymal glands, and lacrimal ducts of cats, dogs, rabbits, horses, cattle, deer, badgers, monkeys, wolves, foxes (definitive hosts) and man being an accidental host. The vectors (intermediate hosts) are non-biting, tear-seeking, diptera flies of family Drosophilidae (fruit flies) Phortica variegata, which feeds on tears of their definitive hosts, including humans. Clinical manifestations include conjunctivitis, lacrimation, itching or pain with foreign body sensation, epiphora, follicular hypertrophy, and less often with severe signs and symptoms such as keratitis, photophobia, ectropion, corneal opacities (due to the migration of worm across the cornea), floaters within the eye chamber leading to visual impairment/blindness. The knowledge and scientific information on human thelaziasis is still unknown or relatively limited to many ophthalmologists and clinicians, and received little attention; hence this comprehensive and systematic review of human thelaziasis, is undertaken to highlight its importance and further research.